Is there a sound democratic case for raising the membership of young people in political parties and trade unions through descriptive representation? - Thomas Tozer (Intergenerational Justice Review)
Young people are seriously under-represented in both political parties and trade unions. I argue that a dependent conception of democracy interested in substantive equality, not merely formal equality, would support addressing this problem through descriptive representation. The essay begins by considering the requirements of democracy, and whether these can support a case for descriptive representation. Although descriptive representation entails democratic costs, there is a contingent case for group representation that is consistent with the aims of democracy. Young people, moreover, satisfy this case in terms of membership of political parties – but less so in the case of trade unions. Finally, the essay considers practical methods for improving young people’s representation in these.